International Migration and Economic Growth in Nigeria - Francis Ebimieseigha (Transpublika Publisher, 2025)
This study seeks to investigate the intricate relationship between intellectual migration and economic growth in Nigeria. Specifically, the study examined how unemployment and corruption drive intellectual migration and assess their implications for Nigeria’s economic growth. Also, the study evaluated the effect of intellectual migration on Nigeria’s innovative capacity and competitiveness. Again, the study analyzed the relationship between intellectual migration and economic growth in Nigeria. Lastly, the study proposed policy recommendations for mitigating intellectual migration and fostering sustainable economic growth. The study adopted a descriptive research design to systematically analyze data trends and patterns of intellectual migration in Nigeria. Data were sourced from International Organization for Migration (IOM), the United Nations (UN), and the World Bank. The study highlighted that intellectual migration, particularly the emigration of skilled professionals, has both positive and negative effects on Nigeria’s economic growth. On one hand, the outflow of human capital contributes to a brain drain, reducing the pool of skilled labor available to drive innovation, productivity, and development within the country. Hence, Nigeria must implement policies that address these root causes and create an environment that encourages skilled professionals to remain in the country.